A study of the effect of injection pressure on the combustion, performance, and emission characteristics of cardanol biofuel blend fuelled compression ignition engine. Issue 1 (4th September 2014) - Dinesha, P.; Mohanan, P.
Abstract The use of biodiesel along with other alternative fuel sources is expected to address the twin problems of pollution and energy security. This study investigates the effect of injection pressure (IP) on the performance, combustion, and emission characteristics of a four‐stroke single cylinder direct injection diesel engine fuelled with a biofuel, namely cardanol‐methanol‐diesel blend (B20M10). The results are compared with baseline diesel operations under standard operating conditions. The biofuel blend B20M10 (20% cardanol, 10% methanol, and 70% diesel) is used as fuel, and the combustion, performance, and emission characteristics are investigated at IP levels of 180, 200, and 220 bar. The test results show that the optimum fuel IP is 220 bar with B20M10. At this optimized pressure, a reduction in CO, HC, and smoke emissions with an increase in the oxides of nitrogen (NOx) and brake thermal efficiency (BTE) are noticed compared with 180 and 200 bar B20M10 operations. When compared with diesel (180 bar IP), B20M10 blend at 220 bar IP gives marginally lower BTE and lower CO and HC emissions, but oxides of nitrogen and smoke are slightly more. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.